2015
DOI: 10.1109/tia.2014.2354745
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a Hydraulic Wind Power Transfer Utilizing a Proportional Valve

Abstract: Abstract-Hydraulic circuits can transfer remarkable amounts of energy in the desired direction without taking large space. To implement this technology for harvesting energy of wind appropriately, models of the system are required. Hydraulic wind power technology has the benefits of eliminating expensive and bulky variable ratio gearbox and its costly maintenance while enabling the integration of multiple wind turbines in a single generation unit. In this paper, the dynamics of different hydraulic elements are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…In 2014, the Energy Systems and Power Electronics Laboratory of the Indiana University--Purdue University Indianapolis (IUPUI) in the US constructed a hydraulic wind power system model that can resist fluctuations of high and low wind speeds by adjusting the simplified second-order model parameters [30]. In 2015, experiments that considered the proportional valve were verified [31], although it remains in the theoretical verification stage because of the lack of a mature product. Therefore, wind power control technology requires further investigation.…”
Section: Development Of Hydraulic Wind Turbine Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, the Energy Systems and Power Electronics Laboratory of the Indiana University--Purdue University Indianapolis (IUPUI) in the US constructed a hydraulic wind power system model that can resist fluctuations of high and low wind speeds by adjusting the simplified second-order model parameters [30]. In 2015, experiments that considered the proportional valve were verified [31], although it remains in the theoretical verification stage because of the lack of a mature product. Therefore, wind power control technology requires further investigation.…”
Section: Development Of Hydraulic Wind Turbine Technologymentioning
confidence: 99%
“…By using the established mathematical model and on the basis of the equations deduced above, Deldar et al [31] compared the obtained results with the experimental results, as shown in Figs. 15 and 16.…”
Section: Compressibility (Hose Dynamics)mentioning
confidence: 99%
“…To derive the state space representation of the hydraulic wind power system, the integrated configuration of the hydraulic components must be considered. Nonlinear governing equations of utilized hydraulic components are provided in [17][18][19]. Using these equations, a nonlinear model of hydraulic wind power transfer systems are proposed in state space representation and experimentally verified.…”
Section: Hydraulic Wind Power System Modelmentioning
confidence: 99%
“…The state variables are the pressure of the pump (P p ), pressure of the Motor A (P mA ), pressure of the motor B (P mB ), the primary motor angular velocity ( mA ), and the auxiliary motor angular velocity ( mB ) [24][25][26][27][28].…”
Section: Hydraulic Wind Power System Modelmentioning
confidence: 99%
“…Using these equations, a nonlinear model of hydraulic wind power transfer systems are proposed in state space representation and experimentally verified. State space representation offers several benefits such as the ease of implementation, stability analysis, and model understanding [23][24][25][26][27].…”
Section: Model Development Of Hydraulic Wind Power Systemsmentioning
confidence: 99%